غضب الشعوب الإسلامية من الإساءة للنبي ـــ صلى الله عليه وسلم - ناصري, عبد العزيز (جامعة الوادي - University of Eloued, 2022)
تُحاول هذه الدِّراسة وضع حدود فاصلة بين الموقف الشَّرعي تُجاه الإساءة للنَّبي -عليه الصلاة والسَّلام- وبين غيره من المواقف غير الشَّرعيَّة، كل ذلك في ضوء ما دلَّت عليه نصوص الكتاب والسُّنَّة، مع ربطها بدراسة تاريخية تتعلق بالأنبياء الذين سبقوه وتعرضوا لنفس المشكل. تظهر بذلك أنَّ محبَّة النَّبي ـــ صلى الله عليه وسلم ـــ الشرعية التي بين الإفراط والتفريط تنبني على تعظيم ومحبَّة الله تعالى، وتتمثَّل في اتَّباع شريعته عقيدة وفقها وسلوكا، وتقتضي الذّبّ عنه على قدر الاستطاعة باليد واللسان والقلب. مع التزام العدل وعدم الخروج إلى الظُّلم. This study attempts to put a boundary between the legal stance towards offending the Prophet Mohamed - peace be upon him - and other non-legal stances; all in the light of what is indicated by the texts in Quran and the Sunnah. Thus, it appears that the legitimate love of the Prophet Mohamed - peace be upon him - that is between excess and negligence is based on glorifying and loving God Almighty, and is represented in following his law in belief, jurisprudence and behavior, and requires defending him as much as possible with hand, tongue and heart. With a commitment to justice and not to go out to injustice.
دراسة تاريخية شرعية
مقال
Keywords: المحبة؛ النبي محمد؛ الإساءة ؛ الدفاع؛ الاساءة; love; prophet Mohamed; defending; justice; offending